Reasons for the death of the Prophet Muhammad (PBUH) and the failure to appoint a successor, from the perspective of Orientalists - أمين, رحيم احمد; زينل, ئاراس فريق (Sulaimani Journal for Humanities, 2019)
One of the significant events that attracted the orientalists is the death of the Prophet Muhammad, and it became the most vital event in the Islamic history due to its importance that led to some serious changes happened after. This event encouraged the orientalists to pay more concern and have a good deal of opinion about it. The study tries to collect and analyze those points of views by the orientalists through historical and scientific fundamentality in accordance with the Islamic age so as to perceive the facts and objectives. Specifically, when some of those views do not go with historical realties and it's not a correspondent neutrality in the narration of scientific facts. Thus, the study attempts at performing a sufficient analysis in historical aspects since there is a vast gap of difference among the interpretations of this event. It tries to be more neutral in its displaying for the facts without being under religious impacts, and making a reading for those views which is abided by academic principles